The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1097/prs.0b013e3181a8082e
|View full text |Cite
|
Sign up to set email alerts
|

Marjolin’s Ulcer: A Preventable Complication of Burns?

Abstract: Marjolin's ulcer is a rare and aggressive cutaneous malignancy that arises on previously traumatized and chronically inflamed skin, especially after burns. This clinical condition was first described by Marjolin in 1828. The term "Marjolin's ulcer" has been generally accepted to refer to a long-term malignant complication of the scars resulting from burns. However, vaccination, snake bites, osteomyelitis, pilonidal abscesses, pressure sores, and venous stasis may also induce this tumor. Clinically, reports sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 52 publications
2
96
1
10
Order By: Relevance
“…4,9 Although controversial, regional lymphadenectomy in clinically palpable/radiologically suspicious nodes or in pathologically proven high-grade cancers is undertaken by many scholars. 10 Lymphatic 'mapping' and sentinel-node biopsy are not feasible in MUs occurring in areas of extensive scarring due to a low prevalence of detection. 11 In our study, 6 patients underwent inguinal block dissection (which revealed negative nodes in 1 patient) and 1 patient underwent axillary dissection based on clinical and radiological data.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 Although controversial, regional lymphadenectomy in clinically palpable/radiologically suspicious nodes or in pathologically proven high-grade cancers is undertaken by many scholars. 10 Lymphatic 'mapping' and sentinel-node biopsy are not feasible in MUs occurring in areas of extensive scarring due to a low prevalence of detection. 11 In our study, 6 patients underwent inguinal block dissection (which revealed negative nodes in 1 patient) and 1 patient underwent axillary dissection based on clinical and radiological data.…”
Section: Discussionmentioning
confidence: 99%
“…Though the original description of Marjolin's ulcer was in the context of squamous cell carcinoma arising from chronic scarring due to thermal injury, there have been reports documenting the association of both mesenchymal malignancies as well as carcinomas other than squamous cell carcinomas that have arisen from chronic non-thermal injuries [2]. There are two types of Marjolin's ulcers: an acute type that develops within 1 year of injury and a chronic type that develops after a latency period averaging 31 years [3,4].…”
Section: Introductionmentioning
confidence: 97%
“…Less frequently, it manifests as an exophytic lesion that is similar to granular tissue. [7][8][9] Given the nature of diabetic foot wherein ulcers do not go away until they are completely cured, it was hard to suspect carcinoma when the patient was initially hospitalized. Even two years later, the patient did not show any clinical abnormalities except the uncured ulcers and granulation tissue.…”
Section: )mentioning
confidence: 99%
“…[7][8][9] Skin grafting is also actively considered for skin lesion reconstruction. Although preventive lymph node dissection is not recommended, some researchers prefer the technique due to the aggressive nature of Marjolin's ulcers.…”
Section: )mentioning
confidence: 99%